A Simple Electrical Model of the Left Ventricle of the Human Heart - Borquez-Berenguer, J; Acosta-Barbosa, K; Henriquez-Diaz, G (Institute of Electrical and Electronics Engineers Inc., 2021)
In this work, a more intuitive electrical model of the left ventricle is proposed to encourage people from the electrical engineering area to get involved in the area of the medical sciences. Initially, the basic principles of the cardiovascular system are compared with electrical elements. Next, a simplified electrical model is then proposed based on a healthy person s ventricular pressure and volume curves. Finally, the proposed model is validated through numerical simulation and compared with the hemodynamic parameters of a healthy adult s cardiovascular system. © 2021 IEEE.